2018
DOI: 10.3389/fmicb.2018.02270
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Nanoconjugated Teicoplanin: A Novel Tool for Bacterial Infection Site Targeting

Abstract: Nanoconjugated antibiotics can be regarded as next-generation drugs as they possess remarkable potential to overcome multidrug resistance in pathogenic bacteria. Iron oxide nanoparticles (IONPs) have been extensively used in the biomedical field because of their biocompatibility and magnetic properties. More recently, IONPs have been investigated as potential nanocarriers for antibiotics to be magnetically directed to/recovered from infection sites. Here, we conjugated the “last-resort” glycopeptide antibiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 67 publications
4
27
1
Order By: Relevance
“…The urgent need for new potent antibiotics has driven much recent interest in GPAs. For example, chemical synthesis recently resulted in the generation of a plethora of vancomycin derivatives with novel modifications that show superior antimicrobial activities (Okano et al, 2017;Wu and Boger, 2019), while teicoplanin has been conjugated with nanoparticles resulting in increased activity against biofilm-forming pathogens (Armenia et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The urgent need for new potent antibiotics has driven much recent interest in GPAs. For example, chemical synthesis recently resulted in the generation of a plethora of vancomycin derivatives with novel modifications that show superior antimicrobial activities (Okano et al, 2017;Wu and Boger, 2019), while teicoplanin has been conjugated with nanoparticles resulting in increased activity against biofilm-forming pathogens (Armenia et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Although many authors have previously reported that IONPs, as well as other types of metal oxide NPs, possess an intrinsic antimicrobial activity (Gabrielyan et al, 2019;Das et al, 2020;Shkodenko et al, 2020), in the different experiments hereby conducted (i.e., agar diffusion assay, BacLight fluorescence assay, bacterial growth kinetics, CFU measurement) a significant bacteriostatic and bactericidal activity was conferred to IONPs only following their conjugation with teicoplanin and vancomycin. As previously reported (Ebrahiminezhad et al, 2014;Arakha et al, 2015;Dinali et al, 2017;Armenia et al, 2018), naked IONPs can interact mainly via electrostatic interactions with bacterial cell envelopes, arresting transiently cell growth and, in sporadic cases, causing cell death, but this phenomenon greatly differs in magnitude from the potent and selective antimicrobial action of 'last-resort' antibiotics such as GPAs towards Gram-positive bacterial strains. In a recent review, Shkodenko et al (2020) reported that in general naked IONPs have to be used at mg/l concentrations to show some antibacterial activity.…”
Section: Antimicrobial Activity Of Gpa-np Systemsmentioning
confidence: 88%
“…The antimicrobial potential of nanocarried teicoplanin was reported only by Peng et al (2010) , who treated osteomyelitis with teicoplanin-encapsulated biodegradable thermosensitive hydrogel; by Gonzalez Gomez et al (2019) , who tested liposome-encapsulated teicoplanin towards S. aureus ; and by Ucak et al (2020) , who reported teicoplanin delivery in poly lactic-co-glycolic acid NPs functionalized with S. aureus specific aptamers. In 2018, our group succeeded for the first time in conjugating teicoplanin to magnetic IONPs, after their functionalization with (3-aminopropyl) triethoxysilane (APTES; Armenia et al, 2018 ). In the present paper, we have investigated the synthesis and the efficacy of IONPs carrying vancomycin and teicoplanin, as an innovative system for GPA formulation and use.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noted that in vitro guidance can also realize the infection targeting of nanomedicines ( Yu et al, 2020 ). As an example, magnetic targeting has been recently introduced to enhance the accumulation of nanomedicines at infection sites ( Subbiahdoss et al, 2012 ; Armenia et al, 2018 ). Ji et al utilize the magnetic targeting ability of magnetic nanoparticles to deliver glucose oxidase, efficiently eradicating bacterial/fungi biofilms ( Ji et al, 2021 ).…”
Section: Accumulation At the Site Of Infectionmentioning
confidence: 99%